2014
DOI: 10.1371/journal.pntd.0003162
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Immune Response in Human Chromoblastomycosis – A Possible Role for Regulatory and Th17 T Cells

Abstract: BackgroundChromoblastomycosis is a chronic fungal infection that affects skin and subcutaneous tissue. Lesions can be classified in tumorous, verrucous, cicatricial and plaque type. The cellular immune response in the severe form of the disease seems to correlate with a Th2 pattern of cytokines. The humoral immune response also seems to play a role. We intended to explore the populations of regulatory T cells and the Th17 pattern.MethodologyTwenty-three biopsies of verrucous form were obtained from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 50 publications
1
18
1
8
Order By: Relevance
“…Similar to the results of Bursch et al [12], we previously demonstrated that CBM lesions display low expression of TGF-β [8], which could reinforce the hypothesis that CD207-positive dermal cells are a new subpopulation of distinct dendritic cells and that, at least in our study, they seem to cooperate with the cascade of the Th17 immune response [12,14]. …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar to the results of Bursch et al [12], we previously demonstrated that CBM lesions display low expression of TGF-β [8], which could reinforce the hypothesis that CD207-positive dermal cells are a new subpopulation of distinct dendritic cells and that, at least in our study, they seem to cooperate with the cascade of the Th17 immune response [12,14]. …”
Section: Discussionsupporting
confidence: 92%
“…Previously we demonstrated that in CBM lesions a predominance of Th17 cells over Treg cells occurs [8]. The imbalance between the regulator and effector profiles could be a major contributor to the inefficiency of the immune response established in this mycosis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Embora células T reguladoras tenham sido identificadas outrora no microambiente das lesões verrucosas de CBM, nota-se que sua presença e/ou desempenho não são suficientemente capazes de modular a resposta imune de maneira a atingir efetividade ideal para a eliminação do fungo e contenção da doença 26 , o que nos permite explanar no momento sobre as células CD207/IL-17 + se tratarem de outro subtipo de células dendríticas que apesar de guardar semelhanças, não são Langerhans.…”
Section: Células De Langerhansunclassified